Computer-Aided Argument Mapping for Improving Critical Thinking: Think Better! Discuss Better! Write Better! - Sönmez, Elif; Çakan Akkaş, Büşra Nur; Kabataş Memi̇ş, Esra (Bilge Akademi, 2022)
The aim of this study is to investigate the impacts of the use of computer-aided argument maps as a tool to promote prospective teachers’ critical thinking skills and dispositions. In this regard, qualitative research method was used in the study. The data of the research were collected through semi-structured interviews. Study group consists of 30 senior prospective teachers from three different classes studying science teaching at a university in Turkey in 2017-2018 academic year. At these three classes mentioned, individual and collaborative argument maps were created in addition to the ABI (Argumentation-based inquiry) activities. The study group was formed on a volunteer basis with 10 students from each class who were selected from, their course performances into consideration. A computer software was used to create the argument maps. Data obtained from interviews were analyzed through NVIVO program. The results obtained indicated that critical thinking skill sub-dimensions such as explanation, analysis, interpretation, evaluation, Self-correction and critical thinking disposition sub-dimensions such as questioning the reliability of sources, being open and fair-minded, being respectful of differences were emphasized more in the group in which the prospective teachers performed computer-aided, individual and collaborative mapping rather than the group in which only ABI activities were performed.
Keywords: Argument map; Argumentation Based Inqiry; Critical Thinking Skill and Disposition; Argumentation; argumentation; critical thinking skill and disposition; argument map; argumentation based inqiry; Theory and practice of education; LB5-3640; 4. Education